Association Between Medicare Star Ratings for Patient Experience and Medicare Spending per Beneficiary for US Hospitals. (March 2017) - Trzeciak, Stephen; Gaughan, John P; Bosire, Joshua; Angelo, Mark; Holzberg, Adam S; Mazzarelli, Anthony J
Objective: To test the association between patient experience and Centers for Medicare and Medicaid Services (CMS) spending at the hospital level. Methods: Using CMS Hospital Compare data set, we analyzed 2014 data for CMS patient experience star ratings and the hospital Medicare Spending per Beneficiary (MSPB) Measure, which assesses price-standardized, risk-adjusted payments for services provided to Medicare beneficiaries for an episode of care from 3 days before hospital admission to 30 days following discharge. We tested the association using linear regression, adjusting for complexity of care using hospital Case Mix Index (CMI) and for socioeconomic status of the hospital patient population using Disproportionate Share Hospital (DSH) status. Results: The MSPB decreased with increasing hospital patient experience ratings. After adjustment for CMI and DSH, better hospital patient experience was associated with lower spending per episode (5.6% decrease from the lowest to highest patient experience star rating). Conclusion: We found that better hospital patient experience was associated with lower health-care spending. Further research is needed to define what specific elements and phases of the episode of care are driving the association.